Geology, mineralogy, and cassiterite geochronology of the Ayawilca Zn-Pb-Ag-In-Sn-Cu deposit, Pasco, Peru - Benites, D.; Torró, L.; Vallance, J.; Laurent, O.; Quispe, P.; Rosas, S.; Uzieda, M.F.; Holm-Denoma, C.S.; Pianowski, L.S.; Camprubí, A.; Colás, V.; Fernández-Baca, Á.; et al. (Springer Science and Business Media Deutschland GmbH, 2022)
The Ayawilca deposit in Pasco, Peru, represents the most significant recent base-metal discovery in the central Andes and one of the largest undeveloped In resources globally. As of 2018, it hosts an 11.7 Mt indicated resource grading 6.9% Zn, 0.16% Pb, 15 g/t Ag, and 84 g/t In, an additional 45.0 Mt inferred resource grading 5.6% Zn, 0.23% Pb, 17 g/t Ag, and 67 g/t In, and a separate Sn-Cu-Ag inferred resource of 14.5 Mt grading 0.63% Sn, 0.21% Cu, and 18 g/t Ag. Newly obtained U–Pb dates for cassiterite by LA-ICP-MS (22.77 ± 0.41 and 23.05 ± 2.06 Ma) assign the Ayawilca deposit to the Miocene polymetallic belt of central Peru. The polymetallic mineralization occurs as up to 70-m-thick mantos hosted by carbonate rocks of the Late Triassic to Early Jurassic Pucará Group, and subordinately, as steeply dipping veins hosted by rocks of the Pucará Group and overlying Cretaceous sandstones-siltstones of the Goyllarisquizga Group. Relicts of a distal retrograde magnesian skarn and cassiterite (stage pre-A) were identified in the deepest mantos. The volumetrically most important mineralization at Ayawilca comprises a low-sulfidation assemblage (stage A) with quartz, pyrrhotite, arsenopyrite, chalcopyrite, Fe-rich sphalerite, and traces of stannite and herzenbergite. Stage A sphalerite records progressive Fe depletion, from 33 to 10 mol% FeS, which is compatible with the observed transition from low- to a subsequent intermediate-sulfidation stage (B) marked by the crystallization of abundant pyrite and marcasite. Finally, during a later intermediate-sulfidation stage (C) sphalerite (up to 11 mol% FeS), galena, native bismuth, Cu-Pb-Ag sulfosalts, siderite, Mn-Fe carbonates, kaolinite, dickite, and sericite were deposited. This paragenetic evolution shows striking similarities with that at the Cerro de Pasco Cordilleran-type polymetallic deposit, even if at Ayawilca stage C did not reach high-sulfidation conditions. The occurrence of an early retrograde skarn assemblage suggests that the manto bodies at Ayawilca formed at the transition between distal skarn and skarn-free (Cordilleran-type) carbonate-replacement mineralization. Mineral assemblages define a T-fS2 evolutionary path close to the pyrrhotite-pyrite boundary. Buffering of hydrothermal fluids by underlying Devonian carbonaceous phyllites of the Excelsior Group imposed highly reduced conditions during stage A mineralization (logfO2 <  − 30 atm). The low fO2 favored efficient Sn mobility during stages pre-A and A, in contrast to other known ore deposits in the polymetallic belt of central Peru, in which the occurrence of Sn minerals is minor. Subsequent cooling, progressive sealing of vein walls, and decreasing buffering potential of the host rocks promoted the shift from low- (stage A) to intermediate-sulfidation (stages B and C) states. LA-ICP-MS analyses reveal significant In contents in Fe-rich sphalerite (up to 1.7 wt%), stannite (up to 1908 ppm), and chalcopyrite (up to 1185 ppm). The highest In content was found in stage A sphalerite that precipitated along with chalcopyrite and stannite, thus pointing to the early, low-sulfidation assemblage as prospective for this high-tech metal in similar mineral systems. Indium was likely incorporated into the sphalerite crystal lattice via Cu+  + In3+  ↔ 2 Zn2+ and (Sn, Ge)4+  + (Ga, In)3+  + (Cu + Ag)+  ↔ 4 Zn2+ coupled substitutions. Indium incorporation mechanisms into the stannite and chalcopyrite crystal lattices remain unclear.
Keywords: Indium; Critical metals; Central Andes; Cordilleran-type deposits; U–Pb cassiterite geochronology; https://purl.org/pe-repo/ocde/ford#1.05.02